Analisis Pengaruh Debt to Equity Ratio (DER) Terhadap Return on Asset (ROA) pada PT Semen Indonesia Tbk - Dienul Rachmat Sofyan; Nurhayati Nurhayati (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine the effect of Debt to Equity Ratio (DER) on Return On Asset (ROA) at PT. Semen Indonesia Tbk from 2010 to 2018. The writing method used is the quantitative writing method with the type of data used is secondary data in the form of a balance sheet report and a company's income statement for the last 10 years. The data analysis techniques used were DER analysis, ROA, simple regression coefficient, correlation coefficient, determination coefficient and hypothesis test (one sample t-test). The results showed that the Debt to Equity Ratio (DER) had no and significant effect on Return on Assets (ROA), this was because the calculated T value was smaller than the T table (-6,241 <2,262) with a sig value of 0,000. Based on the results of the calculation of the correlation coefficient of 0.911 with a very strong level of closeness and the coefficient of determination of 0.830 which indicates that the contribution of the influence of the variable Debt to Equity Ratio (DER) to Return on Assets (ROA) is 83% and the rest is influenced by other variables. which were not examined in this study.